Theory-guided Therapeutic Function of Music to facilitate emotion regulation development in preschool-aged children - Sena Moore, Kimberly; Hanson-Abromeit, Deanna (Frontiers in Human Neuroscience, 2015)
Emotion regulation is an umbrella term to describe interactive, goal-dependent explicit and implicit processes that are intended to help an individual manage and shift an emotional experience. The primary window for appropriate emotion regulation development occurs during the infant, toddler, and preschool years. Atypical emotion regulation development is considered a risk factor for mental health problems and has been implicated as a primary mechanism underlying childhood pathologies. Current treatments are predominantly verbal- and behavioral-based and lack the opportunity to practice in-the-moment management of emotionally charged situations. There is also an absence of caregiver-child interaction in these treatment strategies. Based on behavioral and neural support for music as a therapeutic mechanism, the incorporation of intentional music experiences, facilitated by a music therapist, may be one way to address these limitations. Musical Contour Regulation Facilitation is an interactive therapist-child music-based intervention for emotion regulation development practice in preschoolers. The Musical Contour Regulation Facilitation intervention uses the deliberate contour and temporal structure of a music therapy session to mirror the changing flow of the caregiver-child interaction through the alternation of high arousal and low arousal music experiences. The purpose of this paper is to describe the Therapeutic Function of Music, a theory-based description of the structural characteristics for a music-based stimulus to musically facilitate developmentally appropriate high arousal and low arousal in-the-moment emotion regulation experiences. The Therapeutic Function of Music analysis is based on a review of the music theory, music neuroscience, and music development literature and provides a preliminary model of the structural characteristics of the music as a core component of the Musical Contour Regulation Facilitation intervention.